Handbook of agricultural economics - Gardner, Bruce L.; Rausser, Gordon C. (Amsterdam ; New York : Elsevier, 2001)
The work of more than 50 years aimed at gaining empirical insight into the production structure of agriculture and the related modes of farmers' behavior is reviewed, and orders of magnitude of the various parameters of interests are quoted. The review follows the lines of the evolution of the pertinent research, and it builds on it in forming a general framework for empirical work. This approach broadens the scope of producers' decisions to include the choice of the implemented technology and it also overcomes statistical problems that have accompanied the relevant research for a long time.
v. 1A. Agricultural production -- v. 1B. Marketing, distribution and consumers -- v. 2A. Agriculture and its external linkages -- v. 2B. Agricultural and food policy.
Includes bibliographical references and indexes.
rpm 23/10/13
Loans
Keywords: Agriculture -- Economic aspects; Farm produce -- Marketing; Agricultural credit; Agricultural productivity